Usefulness of the rapid determination system of viral genome sequences in human stool specimens - Miyoshi, Masahiro; Yoshizumi, Shima; Ishida, Setsuko; Komagome, Rika; Nagano, Hideki; Kudo, Shinichi; Okano, Motohiko (Journal of virological methods, 2012)
► The rapid determination system of viral genome sequences (RDV) was applied for the detection of viral genomes in human stools. ► The effect of nuclease treatment of the RDV method was examined. ► The RDV method has potential for the detection of viral genomes in stool specimens. ► The procedure without a step of nuclease treatment appears to be sensitive. The rapid determination system of viral genome sequences (the RDV method) consists of detecting and determining the nucleotide sequences of viral genomes without using specific primers. To evaluate the usefulness of the RDV method, the detection of human norovirus (NV) genomes in stool specimens was investigated. In addition, the effect of nuclease treatment of the process was examined. A total of 23 human stool specimens were used, all of which were collected from patients with acute viral gastroenteritis, and were shown to contain NV genomes and also determined the cDNA copy numbers by the real-time reverse transcriptase-polymerase chain reaction. NV genomes were detected by the RDV method with nuclease treatment in nine specimens containing cDNA copies ranging between 6.2 × 10 9 and 9.8 × 10 11/g stool. In contrast, NV genome was found by the method in 15 specimens without nuclease treatment and the number of NV cDNA copies ranged between 1.2 × 10 6 and 9.8 × 10 11/g stool. These results suggest that the RDV method has potential for detecting viral genomes in stool specimens. The procedure without a step of nuclease treatment appears to be sensitive.